SISTEM INFORMASI DATA ATLET PADA KONI PROVINSI BANTEN - Mochamad Yusuf Romdoni; Irma Yunita Ruhiawati (LPPM Unbaja, 2020)
KONI (Indonesian National Sports Committee) Banten Province is an organization that acts as the parent in the field of sports that continues to foster outstanding athletes from several categories at the local, national, and international levels. In the world of sports, Koni plays an important role in cultivating and fostering athletes. To determine qualified athletes from various categories so that they are ready to take part in a sporting event can be seen from their physical condition and achievements. In this athlete's recommendation must go through the calculation stages manually from physical records, achievements and all trainers who understand it. To solve this problem, we need a system to help process athlete data from several categories which are then used as recommendations for athletes who are ready to be included in an event. Athlete data information systems are built on the basis of assisting in athlete data processing to be more effective and faster, this system is designed with the Waterfall development method in which the program flow design uses Flowcharts so that it becomes clearer how the athlete's information system can run according to good data processing mechanisms from the start of input, process and output. The programming language used is a visual basic language that has been popular and has proven its ability in handling data processing, which on this occasion the database is MySQL. This information system is certainly not immune to weaknesses whose hopes for the future to continue to be developed in order to continue to be useful and easy to operate.